Effect of pouring temperature on microstructure and durability of DD419 single crystal superalloy - ZHANG Hui; DING Qiang; LIU Jide (Journal of Aeronautical Materials)
The creep rupture properties of DD419 single crystal superalloys，fabricated at varying pouring temperatures were examined under conditions of 850 ℃/650 MPa，1050 ℃/190 MPa and 1100 ℃/130 MPa. SEM，EDS and TEM were used to analyze the microstructure and component segregation to study their effects on the durability. The results show that as the pouring temperature decreases，the primary dendrite spacing of the alloy widens，the eutectic content and the number of micropore increase，and the γ′ phase size diminishes. Under high temperature/low stress（1100℃/130 MPa），the γ′ phase size exerts a more pronounced influence on durability than do micropore and residual eutectic content. The finely dispersed γ′ phase enhances the alloy’s durability under all three test scenarios，with the alloy poured at 1500 ℃ exhibiting optimal durability. At intermediate temperature/high stress condition（1050℃/190 MPa），the γ′ phase is intersected by numerous dislocations, and dispersed γ′ phase may contribute to dislocation pile-ups. Concurrently，the alloy maintains good elongation at different pouring temperatures；however，as the pouring temperature decreases，section shrinkage decreases under all three test conditions. Pouring temperature has a negligible impact on the the alloy’s fracture morphology. Specifically, the γ′ phase near the fracture surface of the specimen tested under 850 ℃/650 MPa condition remains cubic morphology，with a mixed -mode fracture mechanism. Under other durability parameters，the γ′ phase assumes a rafted configuration，leading to an all-micropore aggregation fracture mechanism.